KAJIAN ISLAM TERHADAP KONSEP ZAKAT DAN PAJAK PADA ERA MODREN - Johan Alamsyah (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
This research is taken in order to analyze the implementation of zakat and tax policy in Indonesia as well as to discuss management changes in zakah organization after a new policy regulated in 2003 was implemented. The research is a field research using the documentation, interviews, and literacy study as method to obtain data. The data then will be analyzed using descriptive and interpretative method. The result shows that government policy has been applied in the Zakah Administration Organization and Tax Services Office in accordance with the regulations in the Act. Zakah management does not change after this policy compared to before it presence. Although the amount of funds collected decreases, the cause was from external factor, i.e.